2018
DOI: 10.2147/ndt.s170645
|View full text |Cite
|
Sign up to set email alerts
|

Low hedonic tone and attention-deficit hyperactivity disorder: risk factors for treatment resistance in depressed adults

Abstract: BackgroundThe burdens imposed by treatment-resistant depression (TRD) necessitate the identification of predictive factors that may improve patient treatment and outcomes. Because depression and attention-deficit hyperactivity disorder (ADHD) are frequently comorbid and share a complex relationship, we hypothesized that ADHD may be a predictive factor for the diagnosis of TRD. This exploratory study aimed to determine the percentage of undetected ADHD in those with TRD and evaluate factors associated with trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…There is increasing evidence that improved management of ADHD can help a range of co-occurring health problems, in addition to reducing the core symptoms and impairments of ADHD. For example, ADHD is associated with treatment resistance in comorbid depression [ 99 ] which may be reduced by regular treatment for ADHD [ 88 ]. Rates of depression, mania, emotional dysregulation and substance abuse may all reduce during treatment of ADHD with stimulant medication [ 30 , 100 ].…”
Section: Results and Consensus Outcomementioning
confidence: 99%
“…There is increasing evidence that improved management of ADHD can help a range of co-occurring health problems, in addition to reducing the core symptoms and impairments of ADHD. For example, ADHD is associated with treatment resistance in comorbid depression [ 99 ] which may be reduced by regular treatment for ADHD [ 88 ]. Rates of depression, mania, emotional dysregulation and substance abuse may all reduce during treatment of ADHD with stimulant medication [ 30 , 100 ].…”
Section: Results and Consensus Outcomementioning
confidence: 99%
“…Individuals with unrecognised ADHD might present to adult services with related or comorbid symptoms, which may take precedence in diagnosis and subsequent treatment. It was suggested that treatment efficacy of other disorders is limited when the underling ADHD is not treated (Katzman et al, 2017; Sternat et al, 2018). This finding has important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis reported that anhedonia might be related to poor response to antidepressants (Noma et al, 2019). Patients with treatment‐resistant MDD had higher severity of anhedonia, suicidal ideation (Sternat et al, 2018), and a greater number of past suicide attempts (Sagud et al, 2013) than non‐treatment‐resistant individuals. While we did not address treatment resistance, anhedonia might contribute to the suicidal behavior in these patients.…”
Section: Discussionmentioning
confidence: 99%